ROOT-KNOT AND LESION NEMATODES IN COFFEE SEEDLINGS PRODUCED IN THE STATE OF MINAS GERAIS, BRAZIL - Terra, Willian César; Pereira da Silva, Júlio Carlos; Campos, Vicente Paulo; Salgado, Sônia Maria de Lima (Coffee Science - ISSN 1984-3909, 2018)
Understanding the mechanisms of plant-parasitic nematodes (PPN) dispersion is vital to improve control strategies aiming to restrict dissemination of these plant parasites. In the present work, we evaluated the presence of PPN in Arabic coffee (Coffea arabica) seedlings produced in commercial nurseries in Minas Gerais, state, Brazil. A total of 2830 samples obtained from 318 coffee nurseries, in 84 counties within the South and Zona da Mata regions in Minas Gerais, Brazil and representing more than 62 million coffee seedlings, were analyzed. Meloidogyne spp. was identified in 11 samples from four counties. Pratylenchus spp. and Rotylenchulus reniformis were detected in 281 and 47 samples, respectively. According to the Regulatory Instruction N° 35 from the Ministry of Agriculture, Livestock and Food Supply (MAPA), in Brazil, coffee seedlings infected by Meloidogyne spp. are prohibited for commercialization and/or planting. However, such restrictions do not apply to other PPN. Therefore, seedlings sold in Minas Gerais may constitute sources of dissemination for root-lesion nematodes (Pratylenchus spp.) and the reniform nematode (R. reniformis).